Following the Science to Generate Well-Being: Using the Highest-Quality Experimental Evidence to Design Interventions - Donaldson, Stewart I.; Cabrera, Victoria; Gaffaney, Jaclyn (Frontiers in Psychology, 2021)
The second wave of devastating consequences of the COVID-19 pandemic has been linked to dramatic declines in well-being. While much of the well-being literature is based on descriptive and correlational studies, this paper evaluates a growing body of causal evidence from high-quality randomized controlled trials that test the efficacy of Positive Psychology Interventions. This systematic review analyzed the findings from 25 meta-analyses, 42 review papers, and the high-quality randomized controlled trials of Positive Psychology Interventions designed to generate well-being that were included within those studies. Findings reveal Positive Psychology Interventions have the potential to generate well-being even during a global pandemic, with larger effect sizes in non-Western countries. Four exemplar Positive Psychology Interventions—that have been tested with a high-quality randomized controlled trial, have positive effects on well-being, and could be implemented during a global pandemic—are presented and discussed. Future efforts to generate well-being can build on this causal evidence and emulate the most efficacious Positive Psychology Interventions to be as effective as possible at generating well-being. However, the four exemplars were only tested in WEIRD (Western, Educated, Industrial, Rich, Democratic) countries but seem promising for implementation and evaluation in non-WEIRD contexts. This review highlights the overall need for more rigorous research on Positive Psychology Interventions with more diverse populations and in non-WEIRD contexts to ensure equitable access to effective interventions that generate well-being for all.